Emotional intelligence as alternative for the prevention of the psy-chological abuse in the couple. - Blázquez Alonso, Macarena; Moreno Manso, Juan Manuel; García-Baamonde Sánchez, Mª Elena (Anales de Psicología / Annals of Psychology, 2009)
The article emphasizes the need of the employment of the emotional intelligence as a constructive alternative for the prevention of the psychological abuse in the couple. Basing on the researches that affirm that habitually the manifestations of psychological abuse in the couple are before the physical (Follingstad, Rutledge, Berg, Hause & Polek, 1990; Loring, 1994; O'Leary, 1999) and that the impact in the victims is equal or superior to the caused one for the physical abuse (Henning & Klesges, 2003; Marshall, 1992; Sackett & Saunders, 1999; Street & Arias, 2001), we emphasize the need of a preventive primary intervention. It treats that victims and aggressors break with the stereotypes marked by the genre and learn across the emotional intelligence to establish relations of couple based on the empathy, the dialog, the negotiation, the cooperation and the constructive resolution of conflicts. The analysis of the emotional compe-titions carried out from the model multifactorial of Baron (1997) helps our thesis on the importance of an integral prevention that involves in his measures both women and males and avoids to incur the deceitful percep-tion of considering the violence to be a problem "women's patrimony" (Bonino, 2000).